Role of Homestay for Promotion of Rural Tourism - Subedi, Bed Kumari (Rural Development Journal, 2019)
Among various tourists are attractions in Nepal. The area boasts natural landscapes, diverse ecosystems, a serene atmosphere, and a variety of ethnic cultures, all of which draw visitors. A study was carried out to investigate the role of Home stays in advancing rural tourism and to identify tourism-related challenges. The participants included locals, hotel owners, domestic and international tourists, government employees, among others, totaling 40 individuals. The researcher actively engaged in gathering primary data through structured and semi-structured questionnaires and key informant interviews. Findings indicate significant tourism potential due to numerous attractions such as lakes, peaks, cultural events, and agricultural sites. However, local residents noted a low number of foreign tourists and expressed enthusiasm for tourism promotion despite challenges like inadequate coordination between authorities and local promoters, as well as limited funding.